TINDAKAN SOSIAL PENGGUNAAN SIMBOL AGAMA DALAM POSTER KAMPANYE LEGISLATIF TAHUN 2019 DI PROVINSI BANTEN - Malik, Abdul; Astuti, Marlina Tri; Putri, Liza Diniarizky (Ilmu Komunikasi, FISIP Universitas Pasundan, 2021)
This study discusses the phenomenon of the use of religious attributes in campaign posters that occurred during the general elections (elections) in 2019, especially in the selection of legislative candidates in Banten Province who were the subject of research, which we know that religious attributes are often used by Muslim communities in Banten in conducting worship or religious activities, but the political elite using religious attributes as a political message in this campaign poster makes a shift in meaning and the motives used. To examine the identification of the problem the researcher used Max Weber's Social Action Theory and Husserl's phenomenological method, interpretative paradigms and qualitative approaches to look for explanations about events and interpret phenomena that occur, in collecting data researchers conducted observations, in-depth interviews, documentation and literature presentations. The results of this study indicate that the motives carried out by legislative candidates in using religious attributes in the campaign poster are because of the disclosure of identity, habits, image formation and culture. For symbolic meaning in daily life and politics used to worship and religious activities, respect religious people and attend formal activities. Keywords: Husserl's Phenomenology, Meaning, Political Communication, Social Action